Gender-Sensitive Peer Counselling Groups in Times of Conflict Reflections on a Self-Help Support Group in Berlin (Proceedings of the International Conference on Future of Women, 2020)
The arrival of stark number of forcibly displaced refugees in Germany since 2015 has ledto increased challenges in the mental health care system. The system was overburdened, andtherefore innovative approaches to health care for refugees were necessary in order to gainknowledge about their expansion and admission to regular care. To increase knowledge of refugeesregarding mental health services and to provide practical support, a manual for peer-to-peercounseling was developed at Charité University Medical Center Berlin and refugees were trained aspeer counsellors. This paper aims to give an overview of previous peer support interventionspublished in literature and to also point out to the preliminary results from the interventionconducted at the Charité. Good practices and recommendations for peer interventions are provided.Qualitative interviews were conducted with the group participants, and results show that peer groupshelped refugees in sharing experiences, in giving ideas for possible solutions, in buildingsocial/friendship networks, and in providing a safe place for discussions. The results of our studysuggest that integrating gender-sensitive peer support approaches in the mental health services forrefugees may benefit the public health by reducing both need and demand for these services.
Keywords: refugees; mental health; public health; peer support; self-help interventions; culture accessibility; self-management; stepped care collaborative model